Strengthening Religious Moderation of Teachers at Insan Prestasi School Denpasar - Sudarsana, I Ketut; Perbowosari, Heny; Linggih, I Nyoman; Binawati, Ni Wayan Sariani; Wiguna, I Made Arsa (Universitas Pendidikan Ganesha, 2022)
This community service aimed to strengthen the religious moderation of teachers at Insan Prestasi School Denpasar. Education is a significant factor in building a tolerant educational environment for all religious adherents. The implementation of religious moderation in education was to build a sense of mutual understanding between students from an early age who have different religious beliefs. Thus, both the curriculum and the books applied at schools should be curriculums that contain the values of pluralism and religious tolerance. The methods used in this community service were lectures, questions and answers, and assignments. Collecting data used observations, interviews, and questionnaires for participant evaluation and evaluation of activity implementation. The results of this community service showed that Insan Prestasi School teachers understood the concept and implementation of religious moderation at schools. Furthermore, teachers can instill the values of multiculturalism, bring religious messages more peacefully, and spread human values to students at school.